Corporate taxes reduce investment: New evidence from Germany - Sebastian Link; Manuel Menkhoff; Andreas Peichl; Paul Schüle (CESifo GmbH, 2022)
This policy brief provides novel empirical evidence on the causal effect of increasing corporate taxes on firm investment. The study combines unique data on investment plans and their realizations of firms in the German industrial sector and data on more than 1,400 local tax changes in the specific system of business taxation in Germany. We show that firms reduce their investments if corporate taxes were increased. An increase of corporate tax rates to stabilize fiscal revenues would be especially costly during recessions. We conclude that fiscal policy should therefore avoid higher corporate taxation in times of economic crisis. Moreover, our results have implications for the op-timal design of fiscal federalism in Germany. Strong dependencies of municipalities on local business tax revenues should be avoided, as they can be very harmful during recessions.
Keywords: 330